Gender Difference in Perception and Care- Seeking for Illness Among Under Five Children in Rural Areas of Bijapur District, Karnataka - Shashank KJ; Angadi, MM (National Journal of Community Medicine, 2016)
Background: Gender is a common term where as gender discrimination is meant for women, because females are more often the victims..Gender discrimination is due to the attitude and behaviour of the society towards the girl child. Objective: To assess the Perception and Care- Seeking for Illness among under five children by the parents in the rural areas of Bijapur district. Materials and Methods: A Cross Sectional Study was conducted across the ten Villages of Bijapur District from January 2013 to November 3013.A total of 1046 children were included in the study. Data was collected in a Pre tested, Pre designed, Semi structured Questionnaire by interview technique. Results: Around 41% (42% Male and 39.2% Female) of children had suffered from illness in the past one month. Parents spent higher amount for the treatment of male children. Conclusion: The time lag to avail treatment was less for male children and the amount spent for the treatment was also higher for Male children shows the affinity of the Parents towards the Male children.